EXPLORING THE ASSOCIATION OF CARIES EXPERIENCE WITH SOCIAL AND BEHAVIOURAL FACTORS AMONG SCHOOLCHILDREN FROM IASI, ROMANIA - Dana Baciu; Ioan Danila; Carina Balcos (Romanian Society of Oral Rehabilitation, 2013)
Aim of the study To explore the relationship between sociodemographic and oral health behavioural factors with dental caries experience in 6-8- and 11-13-year-old schoolchildren from Iasi. Materials and Methods: A cross-sectional study of 306 in first grade and 278 in sixth grade children was conducted in Iasi in 2012. Information on child socio-demographic characteristics and dental behaviours was collected through questionnaires. Clinical examinations were performed by one trained dentist using the ICDAS II system and caries experience was measured using dmfs/DMFS index. Oral hygiene status was assessed using the Silness and Loe plaque index. The association of sociodemographic and behavioural characteristics and oral hygiene status with caries experience (dmfs/DMFS) was assessed using negative binominal regression models. Results: For 6-8 years old children, socio-economical position, sugary food consumption between meals, treatment and dental pain as reason for the last dental visit and oral hygiene status were found to be significantly associated with dental caries experience in both unadjusted and adjusted models. For 11-13 years old children, oral health status and relatives supervision when child not at school were strongly associated with high levels of caries experience, while all the other factor were not significantly associate with caries experience in both unadjusted and adjusted models. Conclusion: Sociodemographic and behavioural variables and oral hygiene status were found to be risk factors for caries experience in 6-8-yr-old children, while the first two indicators were not significantly associated in 11-13-yr-old children. Epidemiological data can be used for improved public oral health service planning and resource allocation within the region. Future oral health promotion and education programmes should address these risk factors for dental caries experience.